2023
DOI: 10.18564/jasss.5194
|View full text |Cite
|
Sign up to set email alerts
|

What Matters Most in Supporting Cooperation, the Gossip Content or the Gossiper’s Intention? Simulating Motive Interpretation in Gossip Dynamics

Martina Testori,
Francesca Giardini,
Charlotte K Hemelrijk
et al.

Abstract: Gossip provides individuals a great volume of information, which allows them to make informed decisions and better adapt to the environment around them. Like all pieces of information, however, if not correctly interpreted, gossip can lead to harmful consequences for individuals. Indeed, computational models have portrayed a complex picture on how gossip impacts cooperation, identifying several limitations of the mechanism. Recent theoretical models and empirical studies have shown how interpreting the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…In the short term, sending gossip might not lead to large benefits or costs for senders based on the motivational interpretation of receivers, a finding that resonates with results showing that sharing false gossip does not have negative consequences for senders (Fonseca & Peters, 2021). However, the costs of gossip could reveal themselves in the longer run and future research is needed to test the long‐term consequences of having a negative reputation as a gossiper (Testori et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the short term, sending gossip might not lead to large benefits or costs for senders based on the motivational interpretation of receivers, a finding that resonates with results showing that sharing false gossip does not have negative consequences for senders (Fonseca & Peters, 2021). However, the costs of gossip could reveal themselves in the longer run and future research is needed to test the long‐term consequences of having a negative reputation as a gossiper (Testori et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Lee & Barnes (2021) argued that to understand the consequences of gossip for gossipers, it is imperative to consider how receivers interpret the content of gossip and the motivation behind it. Finally, in a computational model, Testori and colleagues (Testori et al, 2023) showed the impact of motive…”
Section: Interpreting Gossip Motivesmentioning
confidence: 99%
See 1 more Smart Citation